2021
DOI: 10.17977/um064v1i82021p1158-1170
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Vocabulary: Konsep Aplikasi Berbasis Augmented Reality untuk Meningkatkan Penguasaan Kosakata Bahasa Arab

Abstract: Language is a communication tool used by everyone to express their desires. Many languages exist in the world, one of which is Arabic. In Indonesia, Arabic is one of the subjects taught at the kindergarten (TK) level with students being introduced to Arabic vocabulary as it is the key language component in order for learners to be able to use the language. However, previous studies found that learning Arabic vocabularies is very challenging for so many people. For this underlying reason, the researcher initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
1
Order By: Relevance
“…It enhances engagement, promotes active and personalized learning, fosters collaboration and critical thinking, and provides a more immersive and contextual learning experience. Teachers should consider incorporating augmented reality technology based on the specific learning goals, resources, and student needs to maximize the benefits of this innovative approach, especially in Arabic language educational contexts [50][35] [9].…”
Section: Learning Methods Using Augmented Reality Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…It enhances engagement, promotes active and personalized learning, fosters collaboration and critical thinking, and provides a more immersive and contextual learning experience. Teachers should consider incorporating augmented reality technology based on the specific learning goals, resources, and student needs to maximize the benefits of this innovative approach, especially in Arabic language educational contexts [50][35] [9].…”
Section: Learning Methods Using Augmented Reality Technologymentioning
confidence: 99%
“…The use of augmented reality technology in learning Arabic can provide several benefits and improve student learning experiences. Firstly, augmented reality can be used to visualize Arabic vocabulary in a more interesting and interactive way [9]. Students can view virtual objects associated with Arabic words, such as images of common objects with their corresponding Arabic labels.…”
Section: Augmented Reality Technology Is Embedded In Learning Arabicmentioning
confidence: 99%
“…AR technology can be widely used as a teaching aid in the future, but only at a basic and non-holistic level (Akashah et al, 2016;Sepasgozar, 2020). As a result, AR technology can be developed and used as a learning medium in the field of education (Alrige et al, 2021;Cahyani et al, 2021). The study of Norabeerah et al ( 2012) demonstrated that AR is used in various fields such as science, astronomy, and English.…”
Section: The Impact Of Augmented Reality On Student Performancementioning
confidence: 99%
“…Despite having a positive impact, third-language effectiveness remains far behind (Akashah et al, 2016). AR technology can be used in games (Sepasgozar, 2020), language translation, vocabulary, sentence reading, and correct pronunciation (Alrige et al, 2021;Cahyani et al, 2021;Fauzan et al, 2020;Lubis et al, 2019). Thus, augmented reality (AR) is a new system that is rapidly expanding and has the potential to improve the effectiveness of teaching and learning in order to meet educational technology goals in the future (Alrige et al, 2020).…”
Section: The Impact Of Augmented Reality On Student Performancementioning
confidence: 99%
“…Dalam tahap ini dilakukan pengujian terhadap seluruh aplikasi yang telah dibangun, dimana semua komponen diuji secara menyeluruh dengan cakupan ujicoba yang lengkap [13]. Dengan melakukan pengujian tersebut diharapkan dapat mengurangi resiko kecacatan dalam aplikasi yang dibangun.…”
Section: E Testingunclassified